Theoretical and Methodological Foundations of the Management by Objectives for the Regional Socio-economic Systems Development - Reznichenko, Sergey M.; Shishkin, Viktor O.; Shichiyakh, Rustem A.; Smolentsev, Vitaly M. (International Review of Management and Marketing, 2016)
The article provides an overview of the fundamental bases of program-oriented management of social and economic systems of the regional economy, determining the concept of program-oriented management of social and economic development as well as structural elements are highlighted and complemented by the authors' principles and laws of the target programming demarcated concept of Management by Objectives and program-oriented planning. The factors constraining the development and application of software and technologies for the management of regional economy`s targeted socio-economic targets. In research the principles of justification of efficiency of realization of a program goals management of development of social and economic systems are specified and added: the resource, assuming accounting of branch and territorial structure of resources, and also compliance of the purposes and resources as the defining line of system of a program goals management. Keywords: program goals management, program and target planning, social economic systems, regional government JEL Classifications: L51; O18; R58